Bureaucratic Responses - Prendergast, Canice (Journal of Labor Economics, 2016)
This paper’s interest is in understanding how bureaucracies should respond to their clients. I claim that because many services are not priced, the responses of bureaucracies to their clients will often be the opposite of the reactions of “normal” firms. Specifically, bureaucracies ignore the most credible complaints from clients, provide the poorest service to clients who value the service most, and require the most red tape for clients who already know their needs.